APLIKASI GENERAL LEDGER TOKO.CAP PADANG PANJANG - Ade Irma Suryani, Nency Extise Putri, An (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2017)
Good application is a determinant factor for the development of a company or governmentagency in the future. However, at this time still many find the process of data processing is stilldone manually that can hinder the development of a system. For that required the applicationto support the information processing activities required. Thus, the authors make anapplication that can facilitate a transaction in order to avoid irregularities in data processingtransactions. The research method used in this data collection process is conducting fieldsurvey and interview with CAP shop in Padang Panjang. Designing Information Systems Dataprocessing transactions using an application based on MySQL database and object-orientedprogramming is PHP with various facilities and facilities in report processing, in thepreparation of reports assisted by using General Ledger. General Ledger generated canimprove the efficiency and effectiveness in report processing, where the required reports canbe produced in a relatively short time and timely in the delivery of reports.Keywords: Application, General Ledger